Rockin’ the Subsurface: Learning Geophysics with ‘Electromagnetic Odyssey’ - Katya Alvarez-Molina; Diego Ruiz-Aguilar; Luis Romero Ramos; Guillermo Sánchez Basoco; Alejandro Méndez González (ReCIBE)
In the education of applied geophysics, innovative learning tools are essential to bridge the gap between theory and practical field experience. Fieldwork is critical for reinforcing classroom knowledge and fostering peer interactions. However, it faces financial costs, physical accessibility, and logistical challenges, which can deter student participation and create equity concerns. To address these issues, adaptable educational models and digitalization are crucial. Integrating Information and Communication Technologies (ICT) has significantly enhanced learning processes, with alternatives like recorded fieldwork videos, high-resolution imagery, and virtual outcrop models gaining prominence, particularly during the COVID-19 pandemic. Through thoughtful design, video games offer educational potential by enhancing motivation and engagement. This paper introduces Electromagnetic Odyssey, an immersive learning tool to overcome traditional field trips’ financial and logistical constraints. The video game considers the application of Electromagnetic methods for groundwater exploration. Electromagnetic Odyssey aims to promote equitable access to quality education and motivate students through well-designed, technology-enhanced activities, aligning with educational principles emphasizing motivation’s importance in learning.